THE ROLE OF PEOPLE’S ORAL CREATION IN THE EDUCATIONAL PROCESS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article discusses the role of folklore in the process of education, the importance of folklore in education, its content and effects.